HUBUNGAN PENERAPAN STANDAR PELAYANAN DENGAN TINGKAT KEPUASAN PASIEN DI PUSKESMAS SUSUA KABUPATEN NIAS SELATAN TAHUN 2024 - Falentina Wau, Falentina; Munthe, Seri Asnawati (Akupun Tour Publisher, 2024)
Background: Health service standards are health service guidelines for officers in providing the best service according to the expected level of performance. Purpose: The aim of the research is to analyze the relationship between the implementation of health service standards and the level of patient satisfaction. Method: The type of research is quantitative research with a cross-sectional research design approach. The research was conducted at the Susua Health Center, South Nias Regency from December 2023 to June 2024. The research population was 38 people who visited the Susua Health Center, South Nias Regency on average per month. The number of samples was determined by a total sampling of 38 people. Primary data collection was carried out directly through questionnaires and observation and secondary data collection were obtained from the Susua Health Center, South Nias Regency. Data analysis was carried out univariate and bivariate. Univariate analysis was carried out to obtain a description of the research variables and bivariate analysis was carried out to test the hypothesis of the relationship between the implementation of service standards (registration, general clinic and pharmacy) with the level of patient satisfaction. Test the hypothesis using the Chi-square test. Disscusion and Conclusion: The results of the hypothesis test show that there is a significant relationship between the application of registration service standards and the level of patient satisfaction obtained by a p-value of 0.000<0.05, there is a significant relationship between the application of general poly service standards and the level of patient satisfaction obtained by a p-value of 0.004< 0.05 and there is a significant relationship between the implementation of pharmaceutical service standards and the level of patient satisfaction obtained by a p-value of 0.027<0.05. This research provides recommendations for improving the quality of registration services, general polyclinic services and pharmaceutical services through training, implementing good standard operational procedures and adequate facilities and infrastructure to increase patient satisfaction at Susua health centers.